Potentially toxic metals in cucumber Cucumis sativus collected from peninsular Malaysia: A human health risk assessment - Yap, Chee Kong; Rosimah Nulit; Aziran Yaacob; Zaieka Shamsudin; Ong, Meng Chuan; Wan Mohd Syazwan; Hideo Okamura; Yoshifumi Horie; Leow, Chee Seng; Ahmad Dwi Setyawan; Krishnan Kumar; Wan, Hee Cheng; et al. (IgMin Research, 2024)
The purposes of this study were to assess the concentrations of Fe, Cu, Ni, Pb, and Zn in the cucumber Cucumis sativus from four farming areas of Peninsular Malaysia, to assess the HHRA of the five heavy metals in the collected samples. The cucumber was collected between May and December 2016 from Kg Ara Kuda (Penang), Kg. Sitiawan (Perak), Kuala Ketil (Kedah) and Jerantut (Pahang) of Peninsular Malaysia. For the edible fruity cucumber, the ranges of metal concentrations (mg/kg dry weight) from the four sites were 9.56-13.6 for Cu, 39.5-109 for Fe, 0.18-2.19 for Ni, 0.74-2.78 for Pb and 17.5-62.0 for Zn. All the target hazard quotient values for Fe, Cu, Ni, Pb, and Zn in adults and children were found below 1.00 for the health risk assessment. The present investigation found no evidence of non-carcinogenic hazards associated with the intake of cucumber in relation to Fe, Cu, Ni, Pb, and Zn. However, it is important to regularly evaluate the levels of heavy metals in vegetables cultivated in these soils and adopt appropriate remediation procedures to reduce harmful effects on human health.